A year amongst the Indians of Queen Charlotte Island, or, An open field for missionary labour [electronic resource] - Poole, Francis ([S.l. : s.n., 1867)
Signed: F.P. Running title: Indians of Queen Charlotte's Island. Excerpt from Mission Life, May 1, 1867. Caption title. Electronic reproduction. Mode of access: Internet. 44